2018
DOI: 10.1590/s0102-865020180050000008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polyamide surgical mesh as an abdominal ventral implant in rabbits

Abstract: Polyamide surgical mesh for hernioplasty presents, in rabbits, excellent biocompatibility, with minimal body adverse reactions and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Considering the biocompatibility of LCM, most studies examined the effects of LCM directly in vivo (either animal or human) showing the success of LCM [ 2 – 4 , 12 , 13 ]. The concern of performing exclusively in vivo studies resides in the fact that there is a huge variation in this type of experiment as different animal species are used (rabbit, pig, rat) and therefore comparison is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the biocompatibility of LCM, most studies examined the effects of LCM directly in vivo (either animal or human) showing the success of LCM [ 2 – 4 , 12 , 13 ]. The concern of performing exclusively in vivo studies resides in the fact that there is a huge variation in this type of experiment as different animal species are used (rabbit, pig, rat) and therefore comparison is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The author's findings were in accordance with the observation of Singh et al, (2008) after abdominal reconstruction with porcine bladder, diaphragm and dermal matrix in rabbits at day 7. Doria et al, (2018) found that inflammatory reaction had mostly subsided by 180 days after surgical repair of abdominal wall defects.…”
Section: Xenogenic Acellular Pericardium Matrix Of Caprine and Porcin...mentioning
confidence: 99%
“…They are constantly in high demand and scientist are seeking additional polymeric carriers for this application [2]. Researchers have documented the attractive clinical application, biocompatibility and potent drug release modulating properties of different aliphatic polyamides [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Yet, there is still not much information regarding their use as extended release drug carriers.…”
Section: Introductionmentioning
confidence: 99%